2021
DOI: 10.1007/s00170-021-08159-z
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnosis of rotating machines based on EEMD-MPE and GA-BP

Abstract: Vibration signals of rolling element bearings (REBs) contain substantial bearing motion state information. However, the property of nonlinear and nonstationary vibration signals decreases the diagnostic accuracy of REBs. To improve the accuracy of fault diagnosis for REBs, an ensemble approach based on ensemble empirical mode decomposition (EEMD), multi-scale permutation entropy (MPE), and backpropagation (BP) neural network optimized by genetic algorithm (GA) is proposed. Firstly, the REBs are decomposed into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In order to improve the accuracy of fault diagnosis, Jin et al [168] proposed an ensemble approach based on EEMD, MPE and GA-BPNN, which could realize the identification of 16 fault patterns. DT is a tree structure, representing a mapping relationship between object attributes and object values.…”
Section: Fault Feature Identification Based On Classical Machine Lear...mentioning
confidence: 99%
“…In order to improve the accuracy of fault diagnosis, Jin et al [168] proposed an ensemble approach based on EEMD, MPE and GA-BPNN, which could realize the identification of 16 fault patterns. DT is a tree structure, representing a mapping relationship between object attributes and object values.…”
Section: Fault Feature Identification Based On Classical Machine Lear...mentioning
confidence: 99%
“…To improve the identification performance of free-conducting particle faults, MPE is extracted to reflect the randomness and mutability of vibration signals. According to the previous researches, there are four parameters should be selected with special care when calculating MPE: the scale factor s, embedding dimension m, delay time τ, and the length of time series N (Jin et al, 2021). It should be noted that setting the initial value of the four parameters is the key to achieving optimal MPE.…”
Section: Feature Extractionmentioning
confidence: 99%
“…(3) The SAWOA is employed to optimize the critical parameters of MPE. In the MPE algorithms, unreasonable parameters setting will make MPE unable to effectively characterize the feature information of the signals (Jin et al, 2021;.…”
mentioning
confidence: 99%
“…ChunYao L [5] used the particle swarm algorithm (particle swarm optimization, PSO) to optimize the BP model, which greatly improved the fault identification rate. By comparing GA genetic algorithm (genetic algorithm, GA) -BP with BP algorithm, Tongtong J [6] et al concluded that the former has fewer iterative steps and could achieve the preset target faster compared with BP neural network fitting data. Sparrow search algorithm(parrow search algorithm, SSA) compared with other group algorithm higher efficiency, faster solution efficiency, but also into the local optimal solution, so this paper adopts a improved sparrow search algorithm (improved sparrow search algorithm, ISSA) the algorithm by BP neural network weights and threshold improved to achieve faster convergence and more accurate results.…”
Section: Introductionmentioning
confidence: 99%